Saving Face While (Not) Talking about Race: How Undergraduates Inhabit Racialized Structures at an Elite and Predominantly White College. (8th September 2021) - Nelson, Ingrid A; Graham, Hannah J; Rudin, Natalie L
Abstract: Through a qualitative case study of an elite, predominantly White, liberal arts college, we find that the unmarked Whiteness of core organizational structures and practices socialized undergraduates to normalize segregation while commodifying diversity. Analysis of publicly available documents (webpages, student newspaper, speeches) and student interviews (n=57) revealed that individuals' attitudes were filtered through organizational structures. When students spoke about race, they tended to use two scripts: diversity script and/or naturalization of segregation script. Yet these culturally legitimated scripts were decoupled from organizational practices. Even though most students claimed to value diversity for its learning potential, many students believed social segregation was "natural, " and either "opted out" of conversations about race or "opted in" to conversations within homogeneous friend groups to maintain respectability within tightly-knit, well-resourced campus networks. The decoupling of structures, scripts, and behaviors motivated undergraduates of all races to adopt White, elite norms for (not) talking about race, which we dub "civilized diversity discourse." Drawing on racialized organizations theory, we argue that the unmarked Whiteness of organizational structures—as well as the college's size and status—shaped students' scripts and behaviors in ways that ensure the enactment and entrenchment of racial ignorance and structural White supremacy.